The potential anti-tumor effect of anesthetics on cancer by regulating autophagy - Wang, Tiantian; Zhou, Zhixia; Jiang, Kai; Wang, Yin; Li, Peifeng; Wang, Shoushi (Frontiers in Pharmacology, 2024)
Autophagy is a conserved, cellular self-degradation system that is essential for maintaining intracellular homeostasis. Increasing evidence suggests that autophagy plays an important dual regulatory role in the development of many human diseases, such as cancer. Recent studies have shown that the autophagy process in tumor cells can be regulated by various stimuli from both intracellular and extracellular environments, including the effects of anesthesia. Anesthetics have been shown to not only have clinical anesthetic and sedative effects but also play important roles in the progression of tumors. The effects of different types of anesthetics on tumors differ. In this review, we summarize the basic information on autophagy, the regulatory function of autophagy in cancer, currently used autophagy-targeted tumor therapy, and the effects of different types of anesthetics on tumor progression. We focus on the molecular mechanisms by which anesthetics exert tumor-inhibiting effects by activating or inhibiting autophagy. Herein, we also explore the potential application of the anesthetic/autophagy system in clinical tumor treatment. These findings provide a theoretical basis for the use of anesthetics during the perioperative period to suppress tumor development and provide insights for autophagy-targeted cancer treatment and drug development.